A Buddhist Perspective on Depression and Ways to Deal with Depression - Metteyya, Beliatte (Journal of International Buddhist Studies, 2019)
Purpose is this article is to present a Buddhist perspective on depression and ways to deal with depression according to Buddhism. First a perspective of depression according to modern psychological findings has been studied and presented to get an understanding of what depression is. Both the nature and the effect of depression have been discussed in this section. Then how these aspects of depression can be explained according to Buddhist Teachings has been studied. Next the causes of depression have been studied first according to modern psychological knowledge and according to Buddhist teachings. Then the research is followed by the ways to deal with depression according to modern psychology followed by a presentation of the ways to deal with depression according to Buddhism.